2008
DOI: 10.1177/0363546507313089
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nonanatomical Insertion and Incongruence of Meniscal Transplants on the Articular Cartilage in an Ovine Model

Abstract: Precise anatomic positioning is mandatory for the potential chondroprotective effect of meniscal transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 55 publications
1
38
0
Order By: Relevance
“…Precise positioning of the anterior and posterior horn seems to be mandatory for achieving an adequate pressure distribution by the meniscal implant. Placement of the posterior horn in a nonanatomic location has been shown to cause a significant increase in the normal pressure over all flexion angles [29], leading to degenerative cartilage changes that are even worse than that after meniscectomy [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Precise positioning of the anterior and posterior horn seems to be mandatory for achieving an adequate pressure distribution by the meniscal implant. Placement of the posterior horn in a nonanatomic location has been shown to cause a significant increase in the normal pressure over all flexion angles [29], leading to degenerative cartilage changes that are even worse than that after meniscectomy [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to its function as a secondary stabilizer, meniscal transplantation can reduce tibial translation and strain on the ACL to near-normal [128]. Fixation technique [35] and positioning [78, 149], as well as sizing of the meniscal transplant, appear to have important impact on the effectiveness and biomechanical result. Experimental studies of meniscal transplantation in animals have demonstrated a chondroprotective effect.…”
Section: Malalignment Loss Of Meniscal Tissue Cartilage Defects Andmentioning
confidence: 99%
“…Additionally, the generally good outcomes following MAT in the present study may be attributable to the surgical technique; suture fixation of the allograft to the capsule combined with trans-tibial bone tunnel suture fixation is the current preferred technique (14,43,44). Techniques using bone plug fixation risk articular cartilage damage and have been associated with a higher failure rate (45,46).…”
Section: Discussionmentioning
confidence: 78%